Extending the firm vs. industry debate: Does industry life cycle stage matter? - Karniouchina, Ekaterina V.; Carson, Stephen J.; Short, Jeremy C.; Ketchen, David J. (Strategic Management Journal, 2013)
A series of Strategic Management Journal studies have debated the extent to which business‐unit, corporate parent, and industry effects explain variance in firm performance. Despite evidence that the industry life cycle impacts competition and performance, the life cycle concept has yet to be incorporated into the firm vs. industry debate. Building on ideas from systems theory, we use longitudinal data from 1,957 firms in 49 industries to examine the relative importance of business‐unit, corporate parent, and industry effects during the growth, maturity, and decline stages of the industry life cycle. We find that corporate parent and industry effects increase as industries move through the life cycle while business‐unit effects decrease between maturity and decline. Thus, the life cycle concept should be incorporated within the firm vs. industry debate . Copyright © 2013 John Wiley & Sons, Ltd